Direct Copper-Mediated C–H Arylation of Triazolo[5,1-c][1,2,4] triazines with Aryldiazonium Salts - Nikiforov, Egor A.; Vaskina, Nailya F.; Moseev, Timofey D.; Fedotov, Victor V.; Aminov, Semen V.; Ulomsky, Evgeny N.; Varaksin, Mikhail V.; Rusinov, Vladimir L.; Charushin, Valery N.; Chupakhin, Oleg N. (Synthesis, 2025)
The C–H functionalization strategy was first applied to the Cu-mediated radical arylation reactions of triazolotriazines with aromatic diazonium salts. A series of C(3)-modified triazolo[5,1-c][1,2,4]triazines were obtained in yields of up to 80% under mild conditions. The radical nature of the reaction mechanism was established by the TEMPO radical trap experiments. The developed method is characterized by its versatile application opportunities, particularly it allows C(3)-arylated azoloazine-derived compounds of various architectures to be available. The elaborated synthetic strategy is of interest in the directed design of azaheterocyclic biomolecules with diverse pharmacological applications.
Keywords: radical reaction; C–H functionalization; arylation; diazo compounds; copper